IMPLEMENTASI KONSEP AL-HAQQ DAN AL-BATHIL DALAM PENDIDIKAN KARAKTER: STUDI KASUS DI PONDOK PESANTREN AL-KIFAYAH RIAU - Wirda Ningsih; Yundri Akhyar (Inteligensi : Jurnal Ilmu Pendidikan, 2026)
The integration of Qur’anic principles concerning Al-Haqq (truth) and Al-Bathil (falsehood) has a significant impact on the formulation of character education for students (santri) implemented in Islamic boarding schools. This study aims to analyze the concepts of Haqq and Bathil in the Qur’an, the principles of Haqq and Bathil in student character education, and their implementation at Al-Kifayah Riau Islamic Boarding School. This research is classified as descriptive qualitative research. The data collection technique used was interviews, while the sampling technique applied was purposive sampling. The findings of this study reveal that student character education based on the concepts of Haqq and Bathil, which refer to absolute truth in spiritual and moral matters, has a strong relationship with the principle of tauhid (Islamic monotheism). In student character education, the concept of Al-Haqq serves as the main foundation. Indicators that can be used to show that students increasingly understand this concept are the track record of improvements in their behavior and actions. The concepts of Haqq and Bathil in character education are expected to become important elements that should be considered in Islamic boarding schools